Choosing the 'right' journal for publication: Perceptions and practices of pandemic‐era early career researchers. Issue 4 (11th August 2022) - Nicholas, David; Herman, Eti; Clark, David; Boukacem‐Zeghmouri, Chérifa; Rodríguez‐Bravo, Blanca; Abrizah, Abdullah; Watkinson, Anthony; Xu, Jie; Sims, David; Serbina, Galina; Świgoń, Marzena; Jamali, Hamid R.; et al.
Abstract: Presents early data from an investigation of the work lives and scholarly communication practices of 177 early career researchers (ECRs) from eight countries. Utilizing mainly coded and textual data from interviews, the paper reports on the findings that pertain to publishing papers in peer reviewed journals. We examine which factors are taken into account when choosing the journal to publish their research in, identifying similarities/differences by country, age, academic status and discipline. Also, explored is whether the pandemic has changed decision‐making. Main findings are that the aim for ECRs is to publish in the 'best' journals, variably measured by prestige, impact factor, standards of peer review and indexation. Appropriateness of audience is the only factor unrelated to the quality of the journal that figures highly among the factors that guide ECRs in the process of selecting a journal. The pandemic has made little difference to the majority of ECRs when they decide on a journal for publishing their research. However, there is a greater awareness of the need for a faster turnover rate, brought on by the importance accorded to speedy publication during the pandemic.